The need for more "College" literacy in support of overall health improvement: Insights from GEAR UP Alabama project - Wilkinson, Larrell L. (Journal of Health and Physical Literacy, 2025)
GEAR UP (Gaining Early Awareness and Readiness for Undergraduate Programs) is a federal program funded by the U.S. Department of Education designed to increase the number of low-income students who are prepared to enter and succeed in postsecondary education. GEAR UP provides grants to states, universities, and school districts to provide services at high-poverty middle and high schools. GEAR UP efforts are significant for many reasons, including college graduates have better self-reported health than high school graduates, and individuals with more education are less likely to report chronic disease conditions (Cutler & Lleras-Muney, 2006). Additionally, individuals with more education are more likely to perform health promoting behaviors (Kawachi, Adler, & Dow, 2010; Cutler & Lleras-Muney, 2006; Ross & Wu, 1995). A novel study by Vable & colleagues (2020) places more emphasis on the association of college education and overall health, demonstrating a strong association for improved physical health for people who received a bachelor’s degree at any point in life beyond normal college age. Still, barriers persist that lower college enrollment and retention of young individuals; impeding from evidence-based educational processes that are directly associated with the positive health measures. Thusly, it is important to better understand how to support at-risk individuals’ participation in natural strategies (i.e., college education) that promote overall health. The purpose of this presentation will highlight lessons learned in improving â€œcollegeâ€ literacy among participants of the 8-year project entitled GEAR UP Alabama (GUA). The presentation will depict the GUA theory of change and draw parallels between college and health literacy in improving college enrollment outcomes through individual and organizational strategies. Finally, insights will be offered to improve overall health literacy through college literacy in support of improved health behaviors and outcomes.